ANALISIS PENGIMPLEMENTASIAN PAIKEM OLEH GURU PAK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI SE-KECAMATAN SIPOHOLON - Damayanti Nababan (Jurnal Christian Humaniora, 2020)
The purpose of this study is to analyze the Implementation of Active, Innovative, Creative, Effective and Enjoyable Learning (PAIKEM) by Christian Religious Education Teachers to Improve Learning Motivation of Class VIII Students of SMP Negeri Sipoholon District in 2018. The hypothesis of this study is the Implementation of Active, Innovative, Creative Learning, Effective and Enjoyable (PAIKEM) by Christian Religious Education Teachers to Improve Learning Motivation of Class VIII Students of State Junior High School in Sipoholon in 2018 ≥ 70% of what was expected, with a research sample of 45 people. Data were collected by a closed questionnaire and validity and reliability were tested. The results of the data analysis show that the Implementation of Active, Innovative, Creative, Effective and Enjoyable Learning (PAIKEM) by Christian Religious Education Teachers to Improve Learning Motivation of Class VIII Students of the State Junior High School in Sipoholon in 2018 ≥ 70% than expected, this is evidenced by the results of a good analysis of 80, 01% and count t table of 3.143 1.684 and. thus Ho is rejected and Ha is accepted. The implication is that if it increases student motivation, teachers must implement Active, Innovative, Creative, Effective and Enjoyable Learning (PAIKEM) in the learning process.BAHASA INDONESIA ABSTRACT: Tujuan penelitian ini adalah untuk menganalisis pengimplementasian pembelajaran aktif, inovatif, kreatif, efektif dan menyenangkan (PAIKEM) oleh guru pak untuk meningkatkan motivasi belajar siswa kelas VIII SMP Negeri sekecamatan Sipoholon Tahun 2018. Hipotesa penelitian ini adalah pengimplementasian pembelajaran aktif, inovatif, kreatif, efektif dan menyenangkan (PAIKEM) oleh guru pak untuk meningkatkan motivasi belajar siswa kelas VIII SMP Negeri sekecamatan Sipoholon Tahun 2018 ≥ 70% dari yang diharapkan, dengan sampel penelitian berjumlah 45 orang. Data dikumpulkan dengan angket tertutup dan telah diuji validitas dan reliabilitasnya. Hasil analisis data menunjukkan bahwa pengimplementasian pembelajaran aktif, inovatif, kreatif, efektif dan menyenangkan (PAIKEM) oleh guru pak untuk meningkatkan motivasi belajar siswa kelas VIII SMP Negeri sekecamatan Sipoholon Tahun 2018 ≥ 70% dari yang diharapkan,  hal ini dibuktikan hasil analisisnya baik sebesar 80,01% dan thitungttabel sebesar 3,143 1,684 dan. dengan demikian Ho ditolak dan Ha diterima. Implikasinya jika akan meningkatkan motivasi belajar siswa guru harus mengimplementasikan Pembelajaran Aktif, Inovatif, Kreatif, Efektif Dan Menyenangkan (PAIKEM) dalam proses pembelajaran.